Effect of Internet-Based Instructional Strategy on Students’ Academic Achievement in Economics: Counselling and Curriculum Inference - Gotip, Nehemiah Wokji; Enem, Uchenna Eucharia; Wilfred-Bonse, Kate Uzoamaka; Bahago, Samaila B; Sa’aondo , Marcellinus (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The study adopted a quasi-experimental research design. The population of the study was 942 Senior Secondary public-school II students in Kaura, Kaduna State. 187 Economics students were sampled from the population. Two research questions and hypotheses guided the study. Data was collected using a Multiple-Choice economic Achievement Test. The instrument was subjected to face and content validation by three experts. The instrument was trial tested on SSS II students in Government Secondary School Kagoro, Kaduna State. The reliability was determined using the Kuder Richardson (K-R20) formula to establish the internal consistency of the instrument, which yielded a reliability index of 0.85. The collected data were analyzed using the mean and standard deviation to answer the research questions, while the Analysis of Covariance was used to test the hypotheses. The study revealed that using an internet-based instructional strategy has increasing positive effects on students' academic achievement in Economics and that gender is not a significant factor in students' academic achievement in Economics. The study recommends, amongst other things, that Economics teachers should use internet-based instructional strategies in teaching Economics and that teachers and students should be counseled on the need to embrace the internet-based instructional approach.